Study on freeze-thaw resistance with NaCl of desert sand engineering cement composites - An, Xue; Che, Jialing; Liu, Haifeng; Yang, Shuyan; Doh, Shu Ing (Elsevier Ltd., 2021)
To test the salt-freezing resistance performance of desert sand engineering cement composite (DSECC) prepared by different types of desert sand, the specimens with 3% NaCl solution on the top surface after 56 days of curing were tested by one-sided freeze-thaw cycles (FTC) and compression test after freezing and thawing. Two desert sands were collected from the Tengger Desert and Mu Us Desert in China, denoted T and M. The appearance, water absorption rate, mass loss rate, relative dynamic elastic modulus and longitudinal ultrasonic speed of the DSECC were tested after 0, 4, 8, 12, 16, 20, 24 and 28 cycles of freeze-thaw. Compressive strength was tasted after 8, 16, 24, and 32 cycles of freeze-thaw. Results show that FTC can accelerate the damage of the appearance. Meanwhile, the water absorption rate increases, the relative dynamic elastic modulus, the longitudinal ultrasonic wave speed, and the compressive strength decreases. Under the same FTC, the salt-freezing resistance performance of DSECC using T has slightly better than that using M.